Лісова рослинність Шосткинського геоботанічного району (Сумська область) - Чорноус, О.П. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2006)
Приводится геоботаническая характеристика лесной растительности Шосткинского геоботанического района, территория которого расположена на северо-востоке Украинского Полесья. Кратко рассмотрены ценотические, флористические и созологические особенности лесов региона. Описаны старые коренные сосновые леса группы ассоциации Pineta hylocomiosa, Pineta myrtillosa, Querceto - Pineta corylosa и Querceto corylosa, типичные для Украинского Полесья и занесённые в "Зелёную книгу Украины". Во флоре лесов выявлено 3 вида, включенных в Приложение I Бернской конвенции, 14 — в Красную книгу Украины и 26 видов, охраняемых на территории Сумской области. The geobotanical characteristic of forest vegetation of the Shostka geobotanical area in the north-eastern part of Ukrainian Polissya is given in the article, as well as the characteristic of woods in the above-menioned area from the point of view of their soils, flora and rarity. Old native pine forests (Pineta hylocomiosa and Pineta myrtillosa, Querceto-Pineta corylosa and Querceto corylosa) typical for Ukrainian Polissya and listed in the Green Data Book [4] of Ukraine are also described. Among the vegetation of the area, 3 species belong to the Supplement I of Bern Convention, 14 are registered listed in the Red Data Book of Ukraine, and 26 species are protected in Sumy Region.